Confidentiality Assessment Model to Estimate Security during Effective E-Procurement Process - Saxena, Surabhi; Agarwal, Devendra (International Journal of Computer Sciences and Engineering, 2025)
Building high secured software components is very important for component-based software projects. The confidentiality of software is one of the important factors determining the security of components. Estimating confidentiality near the beginning in the software development life cycle, particularly at design phase, may help the designers to integrate required highly secured for improving overall security of the developed software. In this paper researcher introduced a metric based model “Confidentiality Assessment Model (CAMOOD)”. This model measure the confidentiality induced by the use of various object-oriented design concepts like data hiding, aggregation, inheritance, coupling and cohesion. Herein, we compared our measurement results with various contributions.